anonymous
  • anonymous
solve dy/dx = e^{x+y} (x+y)^{-1} - 1 y ????
Differential Equations
katieb
  • katieb
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
solve what
anonymous
  • anonymous
\[\frac{ dy }{ dx } = e^{x+y} (x+y)^{-1} - 1 \]
anonymous
  • anonymous
dame i am not at a level like this one, i am sorry

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
ok..., no problem @MikiaseKebede nevermind :)
anonymous
  • anonymous
anonymous
  • anonymous
him
anonymous
  • anonymous
ok
anonymous
  • anonymous
he is good
nubeer
  • nubeer
i think you have to apply the product rule
anonymous
  • anonymous
what did u get it??
nubeer
  • nubeer
hmm i havent solved it just trying to help you with it
nubeer
  • nubeer
or there is another easier way u =x+y du/dx = 1 du =dx
mayankdevnani
  • mayankdevnani
http://mathhelpforum.com/differential-equations/194955-solving-dy-dx-e-x-y.html
mayankdevnani
  • mayankdevnani
solve dy/dx = e^{x+y}
anonymous
  • anonymous
@mayankdevnani No, i mean \[\frac{ dy }{ dx } = e^{x+y} (x+y)^{-1} - 1 \]
anonymous
  • anonymous
let \[z=x+y\]and u have\[\frac{\text{d}z}{\text{d}x}=1+\frac{\text{d}y}{\text{d}x}\]put this in the original equation\[\frac{\text{d}z}{\text{d}x}-1=\frac{e^z}{z}-1\]\[\frac{\text{d}z}{\text{d}x}=\frac{e^z}{z}\]u have a separable differential equation :)
anonymous
  • anonymous
ok @mukushla, then i got \[\int\limits z dz = \int\limits e^{z} dx\] \[\frac{ z^{2} }{ 2 } = e^{z} x\] \[\frac{ (x+y)^{2} }{ 2 } = e^{x+y} x\] Did I miss something?
anonymous
  • anonymous
emm...there is a little mistake in ur separation\[ze^{-z}\text{d}z=\text{d}x\]
anonymous
  • anonymous
\[\int\limits \frac{ z }{ e^{z} } dz = \int\limits dx \]
anonymous
  • anonymous
exactly
anonymous
  • anonymous
\[\frac{ -1 + z }{ e^{z} } = x\] \[\frac{ -1 + x + y }{ e^{x+y} } = x\] \[\frac{ x+y-1 }{ x } = e^{x+y}\]
anonymous
  • anonymous
integration by parts for z :)
anonymous
  • anonymous
\[\int\limits ze^{-z} dz = \int\limits dx\] u = z, \(dv = e^{-z} dz\), then du = dz, and \(v = -e^{-z}\) So \[-ze^{-z} - \int\limits -e^{-z} dz = \int\limits dx\] \[-ze^{-z} - \frac{ e^{-z} }{ \ln e } = x\] then ??
hartnn
  • hartnn
ln e = 1 re substitute z as x+y
anonymous
  • anonymous
\[-ze^{-z} - e^{-z} = x\] \[-(x+y)e^{-(x+y)} - e^{(x+y)} = x\] \[(-x-y - 1) e^{-(x+y)} = x\] \[(1+x+y) =- x e^{(x+y)}\]
anonymous
  • anonymous
did i miss something?
hartnn
  • hartnn
nopes, thats correct. :)
anonymous
  • anonymous
so how to find y?
hartnn
  • hartnn
i don't think, y can be isolated....
hartnn
  • hartnn
http://www.wolframalpha.com/input/?i=%281%2Bx%2By%29%3D%E2%88%92xe%5E%28x%2By%29+solve+for+y
anonymous
  • anonymous
what it means to "W is the product log function"??
hartnn
  • hartnn
even idk that... not a standard function for sure....
anonymous
  • anonymous
ok Thank you all so much! i really appreciate it :)
hartnn
  • hartnn
welcome ^_^

Looking for something else?

Not the answer you are looking for? Search for more explanations.